2022
DOI: 10.3389/fsufs.2022.771041
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Change and Global Sustainable Development Goals

Abstract: Food production for human consumption is a leading cause of environmental damage in the world and yet over two billion people suffer from malnutrition. Several studies have presented evidence that changes in dietary patterns across the world can lead to win-win outcomes for environmental and social sustainability and can complement ongoing technological and policy efforts to improve the efficiency of agricultural production. However, the existing evidence have been compiled in “silos” by a large range of resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 194 publications
0
18
0
Order By: Relevance
“…This finding corroborates studies that revealed that replacing animal-origin foods with plant-based foods might reduce food-related greenhouse gas emissions. Moreover, this might help achieve the 13th Sustainable Development Goal (Climate Action) and the Paris Agreement commitments [161]. It is worth mentioning that plant-based animal-meat analogues do not contribute to growing global health risks, such as antibiotic resistance and pandemic risk [162].…”
Section: Discussionmentioning
confidence: 99%
“…This finding corroborates studies that revealed that replacing animal-origin foods with plant-based foods might reduce food-related greenhouse gas emissions. Moreover, this might help achieve the 13th Sustainable Development Goal (Climate Action) and the Paris Agreement commitments [161]. It is worth mentioning that plant-based animal-meat analogues do not contribute to growing global health risks, such as antibiotic resistance and pandemic risk [162].…”
Section: Discussionmentioning
confidence: 99%
“…The main driver behind global land use change has been our food system. A majority of Earth’s ice-free land is currently used for the purpose of agriculture (crops and livestock production), and ongoing agricultural expansion has been the predominant driver behind ongoing deforestation, resulting in habitat loss, fragmentation, and degradation for native biodiversity and consequently causing their population decline and eventual extinction. , …”
Section: Crop Intensification and Land Savings Debatementioning
confidence: 99%
“…The involvement of a network of subsystem units, which involves different and complex processes, requires intervention in the socio-food system management that combines the communication of food chain agents with functions, structures, and institutions from the economic, social, and environmental aspects. The five subsystems encompass the first subsystem (agriculture), the second subsystem (marketing), the third subsystem (consumption), the fourth subsystem (disposal of food) and the fifth subsystem (environment) [4]. This requires the development of ecological and social aspects embedded in it.…”
Section: The Socio-food Transformation Systemmentioning
confidence: 99%